DETERMINATION OF THE TYPE OF INHERITANCE OF THE “LYRA”, “VELIFEROUS” AND “SIMPLE” FORMS OF THE CAUDAL AND DORSAL FINS IN SWORDFISH (XIPHOPHORUS HELLERI, HENCKLE, 1848) - Scotto, Carlos (2020)
Th e importance of Swordfish (Xiphophorus helleri Henckle, 1848) for current ornamental aquaculture is known. However, despite the diversity of known traits, classical genetic studies to determine the hereditary shape of the caudal and dorsal fins are few. Th e present investigation employing directed crosses was able to identify the dominant form of the caudal fi n of “Lira form” and the dorsal fi n of “Veliferous form”. Both traits were dominant over the recessive trait "Simple form" in both the caudal and dorsal fi ns (F1). Likewise, through directed crosses of the two traits, it was statistically determined by the Chi-Square test that the forms of inheritance of both traits were segregated in the F2 in the Mendelian ratio 9: 3: 3: 1. Th is would allow the genetic improvement of the shape of the fi ns in the Swordfi sh and obtain improved lines with greater commercial value for the ornamental aquaculture.